2021
DOI: 10.1007/s11356-021-16331-x
|View full text |Cite
|
Sign up to set email alerts
|

The mutagenic effect of tobacco smoke on male fertility

Abstract: Despite the association between tobacco use and the harmful effects on general health as well as male fertility parameters, smoking remains globally prevalent. The main content of tobacco smoke is nicotine and its metabolite cotinine. These compounds can pass the blood-testis barrier, which subsequently causes harm of diverse degree to the germ cells. Although controversial, smoking has been shown to cause not only a decrease in sperm motility, sperm concentration, and an increase in abnormal sperm morphology,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
28
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 31 publications
(37 citation statements)
references
References 112 publications
3
28
0
Order By: Relevance
“…Besides the above-mentioned endogenous sources of ROS, a growing list of potential lifestyles and environmental factors have been suggested to contribute to the extreme generation of ROS in semen. These include cigarette smoking ( 71 ), alcohol consumption ( 72 ) and electromagnetic radiations ( 73 ).…”
Section: Origins Of Ros In Semenmentioning
confidence: 99%
“…Besides the above-mentioned endogenous sources of ROS, a growing list of potential lifestyles and environmental factors have been suggested to contribute to the extreme generation of ROS in semen. These include cigarette smoking ( 71 ), alcohol consumption ( 72 ) and electromagnetic radiations ( 73 ).…”
Section: Origins Of Ros In Semenmentioning
confidence: 99%
“…Cumulative studies have shown that some adverse factors, such as new coronavirus [36], Marburg virus [37], chemotherapeutic drug busulfan [38], and heavy metal ion cadmium [39], can damage the BTB, resulting in spermatogenesis disorder and even male infertility. In addition, some studies have shown that some substances, such as manganese [40], nicotine and its metabolites in tobacco smoke [41], and metal oxide nanoparticles [42], can directly pass through the BTB and cause spermatogenesis disorder. Therefore, maintaining BTB integrity is an important basis for normal spermatogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…The inhibited formation of FSH and LH results in the process of spermatogenesis being abnormal. 25 Data obtained from the one-way ANOVA test showed a significant difference in the thickness of seminiferous tubules epithelial between the positive control group and the treatment group with a significance level of 0.000. This significant difference in the thickness of seminiferous tubules was due to the administration of Javanese ginseng root extract in the treatment group.…”
Section: Discussionmentioning
confidence: 96%